Consumption-based responsibility for global warming and the distribution of impacts of swiss climate policy - Florian Landis (Swiss Journal of Economics and Statistics)
Abstract Different consumption patterns have been linked to different levels of responsibility for current greenhouse gas (ghg) emissions, and it is well established that the affluent are responsible for higher levels of global ghg emission than are the poor. Here I couple a life cycle assessment of consumer goods with household survey data about consumption patterns to arrive at household level responsibility for global ghg emissions by consumption category. This allows me to provide a detailed analysis of how different consumption categories contribute to this responsibility. From this, I offer insights into how this information can be used for designing policies that create equitable outcomes. I conclude that the distributional impacts of ghg pricing with revenue recycling will remain unproblematic as climate policy continues to cover more ghgs from more regions. If it is desired that high-income households make a bigger contribution to the emissions reduction effort than others, focusing climate policy on transport (high confidence), eating out, and clothing (both with lower confidence) may provide avenues for achieving that. This is the case, since responsibility for ghg emissions from these consumption categories increases faster with income than it does for other goods.